A Socio-Pragmatics Approach of Refusal Strategies on a Biopic Movie “Sang Pencerah (The Enlightener)” - Hidayati Hidayati; Rima Rahmaniah (Muhammadiyah University of Mataram, 2020)
Refusal isnegative responses to request, invitations, suggestions, offers, and the like which are frequently used in our daily lives (Sadler & Eroz, 2001: 55). Refusing is not just directly by saying no, but it can be an indirect utterance by giving additional explanation or reason, statement of regret, etc.However, the researcher want to analyse the context of Sang Pencerah an Indonesian national heroine from Kauman, Yogyakartascript which is a biopic moviein sociolinguistics perspectives based on socio-pragmatics approach.Sang Pencerah(The Enlightener) is a 2010 Indonesian film is a biopicof Ahmad Dahlanwhich describes how he came to found the Islamic organisation Muhammadiyah.The subject of the study is the script itself with two problem statements, they are; doesindirect refusal strategies classifications are used by the characters in the movie in their conversation, and what indicated of it is applied. To investigate of the problemsanswer, the researcherapplies a theory of refusal strategies from Bebee, Takahashi, and Uliss-Weltz’s(1998). Hence, the researcher used a descriptive qualitative method in analyzing this researchby using the Miles and Huberman theory. In doing the analysis, the researcher found about indirect refusal strategies and the indicated of it is applied by the characters in the conversation of Sang Pencerah script movie. There are conversations using indirect refusal strategies and the types used by the characters in the conversation of the Sang Pencerah conversation script movie are